2020
DOI: 10.1063/5.0008812
|View full text |Cite
|
Sign up to set email alerts
|

Lag-correlated rising tones of electron cyclotron harmonic and whistler-mode upper-band chorus waves

Abstract: Electron cyclotron harmonic (ECH) and whistler-mode chorus waves can contribute significantly to the magnetospheric dynamics. In the frequency-time spectrogram, ECH usually appears as a series of harmonic structureless bands, while chorus often exhibits successive discrete elements. Here, we present surprising observations by Van Allen Probes of lag-correlated rising tones of ECH and upper-band chorus waves. The time lags of ECH elements with respect to chorus elements range from 0.05 to 0.28 s, negatively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It is noteworthy that most of these events do not show coexistence of chorus waves, which are required for the generation of ∼1 s periodic rising and falling tone ECH waves reported by Gao et al (2018) and Gao et al (2020), indicating that new mechanisms are needed to explain the observed rising and falling tone ECH waves with a period of ∼1 min.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It is noteworthy that most of these events do not show coexistence of chorus waves, which are required for the generation of ∼1 s periodic rising and falling tone ECH waves reported by Gao et al (2018) and Gao et al (2020), indicating that new mechanisms are needed to explain the observed rising and falling tone ECH waves with a period of ∼1 min.…”
Section: Discussionmentioning
confidence: 92%
“…(2018) and Gao et al. (2020), indicating that new mechanisms are needed to explain the observed rising and falling tone ECH waves with a period of ∼1 min.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…where n i denotes the electron density of component i, θ ‖i and θ ⊥i denote parallel and perpendicular thermal velocities with respect to the background magnetic field, respectively. Δ i and β i are dimensionless characteristic parameters to describe the depth and width of the loss cone (e.g., Ashour-Abdalla & Kennel, 1978;Gao et al, 2021;Gao, Shang, et al, 2020;Summers & Thorne, 1995;Zhou et al, 2017). The parameters Δ and β are used to represent the loss-cone feature of the electron distribution, which is different from the "loss cone angle" determined by the background magnetic field configuration.…”
Section: Fully Thermal Simulationsmentioning
confidence: 99%